Barnets deltagande i mål om umgängesbegränsningar- En kvalitativ dokumentstudie av domstolsprotokoll - Skogkär,Signe; Kleiman,Julia (2025)
Children who are placed in foster care because of neglect or abuse have the right to maintain the relationship with their parents, as per the Swedish LVU law, though this is more often than not a complex feat to achieve. The Convention on the Rights of the Child states that children who are capable of forming their views shall be given the right to express those views freely in all matters affecting them, and their views shall be given due weight by their age and maturity, as per article 12 of said convention. This study analyzed how children's participation is considered in court records concerning decisions about visitation restrictions between child and parent. The study is a qualitative document analysis of 30 court records from administrative and appellate courts, focusing on children's expressed wishes, emotions, and behavior, as well as how cooperation (or lack thereof) between social services, biological parents, and foster parents affects the care of the children. Data collection was conducted through a purposeful random sampling of court records, and the material was analyzed using thematic analysis. The results indicate that children's wishes are rarely made clear in the records and that decisions are often based on the court’s and social services’ interpretations of the children's behaviors rather than their expressed opinions. Furthermore, the quality of cooperation between social services, foster homes, and biological parents seemingly influences the children’s well-being. The study highlights the importance of ensuring genuine child participation and influence in processes that affect their lives.